Calcium intake on Gramasree male bird’s semen quality - Elangovan, Sabarinath; Murugan, Senthil; Chacko, Biju; Bunglavan, Surej Joseph; Promod, K. (Indian Journal of Animal Nutrition, 2021)
A study was assigned in 18 Gramasree male birds of 32nd weeks of age, randomly distributed to three experimental groups (G1, G2 and G3) with six birds in each group and housed separately in male cages for 91 days. During this experimental period, layer breeder ration (control) was prepared as per ICAR, (2013) recommendations and fed to all experimental male birds. Egg shell powder and shell grit having more than 2 mm particle size was given as free choice after feeding to GII and GIII birds, respectively to meet their extra calcium requirement. The feed intake and body weight were significantly different (p<0.01) between the treatment groups. Egg shell powder and shell grit intake was 0.67 and 0.72 g/rooster/day, respectively. Total calcium intake was 3.20, 3.44 and 3.55 g/rooster/day in G1, G2 and G3, respectively. Semen was collected by abdominal massage at weekly intervals from 33rd to 44th weeks of age and analysed for semen volume, colour, sperm concentration and sperm motility and significantly no difference was found between the groups. The serum Ca and P content, tibial characteristic and tibial-ash were similar in all treatment groups but the tibial calcium content was significantly (p<0.01) higher in shell grit group. It can be concluded that, calcium intake (3.20 g/rooster/day) through feed is sufficient for male birds to meet their calcium requirements and extra egg shell powder, shell grit given as free choice feeding had not influenced the semen qualities without any detrimental effects.